Backflow Power Optimization Control for Dual Active Bridge DC-DC Converters - Fei Xiong; Junyong Wu; Liangliang Hao; Zicheng Liu (Energies, 2017)
This paper proposes optimized control methods for global minimum backflow power based on a triple-phase-shift (TPS) control strategy. Three global optimized methods are derived to minimize the backflow power on the primary side, on the secondary side and on both sides, respectively. Backflow power transmission is just a portion of non-active power transmission in a dual active bridge (DAB) converter. Non-active power transmission time is proposed in this paper, which unifies zero power transmission and backflow power transmission. Based on the proposed index, an optimized control method is derived to achieve both the maximum effective power transmission time and minimum current stress of DAB at the same time. A comparative analysis is performed to show the limitations of the minimum backflow power optimization method. Finally, a prototype is built to verify the effectiveness of our theoretical analysis and the proposed control methods by experimental results.